2009
DOI: 10.4300/jgme-d-09-00017.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Number of Clinics and Panel Size on Patient Continuity for Medical Residents

Abstract: Patient continuity for residents significantly increased with increasing numbers of clinics and decreasing panel size and was significantly influenced by the attending physician.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…These findings describing associations between panel size, number of clinics, and UPC are consistent with prior literature. 9 PHY measures continuity from a different perspective. This measure reflects the percentage of time that residents see their own patients and has been suggested as the most appropriate measure for continuity when evaluating resident outpatient educational experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings describing associations between panel size, number of clinics, and UPC are consistent with prior literature. 9 PHY measures continuity from a different perspective. This measure reflects the percentage of time that residents see their own patients and has been suggested as the most appropriate measure for continuity when evaluating resident outpatient educational experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that clinic time and frequency, as well as patient panel size, affect continuity. [9][10][11] Several structural models have been described and evaluated by internal medicine (IM) residencies throughout the United States. [12][13][14][15][16] Reports from single institutions with innovative education models show conflicting results in patient-provider continuity.…”
Section: Introductionmentioning
confidence: 99%
“…6,8 Despite its importance, studies documenting resident continuity with patients generally illustrate disappointing findings. [18][19][20][21] One study found that pediatrics patients assigned to a resident physician saw their primary physician at only 25% of their visits. 22 Although past studies have demonstrated varied levels of continuity in resident teaching practices, factors that may improve continuity have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…13 By contrast, reducing the size of a PCP's panel has been shown to result in shorter patient wait times for empaneled appointments, longer visits, 14 and enhanced overall continuity of care. 15 Although these improvements lead to higher overall patient and physician satisfaction, 16 smaller panels may cause difficulties in finding a PCP. Continuity of care has been associated with improved preventive care, lower costs, and an improved experience for patients and physicians.…”
Section: Is a Primary Care Panel Size Of 2500 Patients Reasonable?mentioning
confidence: 99%